A novel method to predict thermal conductivity of NaCl/water based MCNT nano-suspesnion for cold energy storage. (February 2019) - Huang, Yaoting; Cong, Lin; She, Xiaohui; Li, Yongliang; Ding, Yulong
Abstract: As a typical cold storage media working at sub-zero temperature, NaCl-water solution as a phase change material (PCM) with -21 o C melting point has been selected in this study. 0.0625 vol.%-0.5 vol.% multi-wall carbon nanotube (MCNT) was dispersed in the NaCl-water basefluid via ultra-sonicating to make nano-suspension. The viscosity of MCNT-NaCl-water was measured and the experimental results fitted well with the modified Krieger-Dougherty (K-D) model. The structure of MCNT cluster was derived from the fitting of viscosity data, showing that the lower the temperature, the larger the cluster size could be. Benefited from the MCNT cluster parameter, the thermal conductivity of MCNT-NaCl-water was predicted by modified Hamilton-Crosser (H-C) model, in which the MCNT cluster was considered as a whole part with its equivalent thermal conductivity. In addition, thermal conductivity experiment was also conducted to compare the measured value with the calculated value. The results indicated that the traditional H-C model underestimates the measured thermal conductivity by a large margin while the approach proposed in this paper shows good accuracy. Moreover, it is also found that MCNT will improve the thermal conductivity more significantly at low temperature than at high temperature.